PENGUATAN HUBUNGAN BILATERAL INDONESIA – AMERIKA SERIKAT MELALUI PROGRAM DIPLOMATS GO TO CAMPUS BAGI MAHASISWA HUBUNGAN INTERNASIONAL UNIVERSITAS TANJUNGPURA - Alunaza, Hardi; Nugrahaningsih, Nurfitri; Fahriansyah, Ori; Patriani, Ira (Jurnal Abdi Insani, 2024)
The United States is a major power country that has a long track record of cooperation with Indonesia. On the other hand, Indonesia as a country that currently continues to support Palestinian independence can also be a sensitive issue for relations between the two countries. The aim of this service activity is to provide education about Indonesia-United States relations and to dispel sensitive issues occurring between the United States and Middle Eastern countries which are considered to be an obstacle to build good relations between Indonesia and the United States. This community service aims to increase people to people contact and provide education regarding bilateral relations between Indonesia and the United States. This activity will be carried out in May 2024 using three methods, preparation and delivery of educational material, question and answer session, and reporting. After carrying out this activity, International Relations study program students became more concerned about increasing people to people contact through increasing understanding of the differences between the two countries, democratic values, and opportunities for prosperity for both countries. Apart from that, students understand the functions and duties of diplomats as representing, promoting, protecting, negotiating and reporting. Students also understand the strategic interests of Indonesia and the United States. Also, there is a Comprehensive Strategic Partnership between Indonesia and the US and an action plan for Indonesia and America for 2024-2028. Including the implementation of shared values ​​and partnerships between Indonesia and the United States. Such as assistance in developing the quality of education in Indonesia, humanitarian assistance, and cultural development between the two countries.